The Relationship between Body Dysmorphic Disorder and Emotion Regulation in Individuals Seeking Cosmetic Surgery: The Mediating Role of Self-Concept - Namadmaliani Zadeh, Zeinab; Johari Fard, Reza; Talebzadeh Shoushtari, Marzieh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2025)
Background: Body dysmorphic disorder significantly reduces self-esteem and may be prevalent among individuals seeking cosmetic surgery. Aim: Investigating the mediating role of self-concept in the relationship between body dysmorphic disorder and emotion regulation in individuals seeking cosmetic surgery in Ahvaz. Methods: This descriptive-correlational study employed structural equation modeling. From individuals with body dysmorphic disorder who visited beauty clinics in Ahvaz in 2022, 180 participants were selected using a convenience sampling method. Data were collected using the Body Dysmorphic Metacognitive Questionnaire, Emotion Regulation Questionnaire, and Self-Concept Questionnaire. Pearson correlation coefficient and structural equation modeling using AMOS and SPSS version 23 were employed for data analysis. Results: The results indicated that the model fit indices were within the acceptable range. There was a significant negative correlation between body dysmorphia and positive emotion regulation (reappraisal) (r=-0.37), a significant positive correlation between body dysmorphia and negative emotion regulation (suppression) (r=0.42), and a significant positive correlation between body dysmorphia and self-concept (r=0.22). Furthermore, the relationship between suppression and reappraisal with body dysmorphia was significantly mediated by self-concept. Conclusion: Self-concept plays a significant role in the relationship between body dysmorphic disorder and emotion regulation. Individuals with higher levels of body dysmorphia may exhibit poorer emotional regulation strategies and lower self-confidence. These results highlight the importance of addressing self-concept in the treatment of body dysmorphic disorder.